Establishing a 3D culture system for early organogenesis of monkey embryos ex vivo and single-cell transcriptome analysis of cultured embryos - Nianqin Sun; Honglian Shao; Youyue Zhang; Baiquan Ci; Hui Yao; Bing Bai; Tao Tan (STAR Protocols, 2024)
Summary: Creating in vitro culture platforms for monkey embryos is crucial for understanding the initial 4 weeks of early primate embryogenesis. Here, we present a protocol to culture cynomolgus monkey embryos in vitro for 25 days post-fertilization and to delineate the key developmental events of gastrulation and early organogenesis. We describe steps for culturing with a 3D system, immunofluorescence analysis, single-cell RNA sequencing, and bioinformatic analysis.For complete details on the use and execution of this protocol, please refer to Gong et al. (2023).1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.